Development of Liveworksheet-based Interactive LKPD on The Local Biodiversity â€œKratomâ€ to Support the P5 Project - Oktaviona, Erika; Qurbaniah, Mahwar; Setiadi, Anandita Eka (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop valid and practical Liveworksheet-based interactive LKPD on the local biodiversity â€œKratomâ€ to support the P5 Project. This research method used research and development (R&D) with the 4D model consisting of 4 stages: Define, Design, Develop, and Disseminate. The developmental research was conducted at SMAN 3 Pontianak, with teachers and students in class X as the research subjects. The research instrument used an interview and a questionnaire with a Likert scale validity data analysis and a Guttman scale for practicality data analysis, which analyzed descriptively qualitative and quantitative. The results showed that the interactive E-LKPD developed a very valid category based on the validator's assessment of the material experts, with an average of 94.2%, media experts 96.3%, and linguistics 91.9%. Based on various factors such as appearance, presentation of materials, usefulness, and response to project-based learning activities. The results of the practicality of the student questionnaire response were 90% in the small-scale trial and 88.4% in the large-scale trial. So, the developed Liveworksheet-based interactive LKPD is categorized as very practical. Based on these findings, the development is categorized as very valid, very practical, and can be utilized in learning biology on biodiversity material to support P5 project.